Estudo de ondas planetárias nas localidades de Ascension Island, São João do Cariri e Costa Rica. - MELO, Shayne Halyson Pereira de. (2022)
Wind measurements were collected by SKYiMET meteoric radar, for the locations of Ascension Island (7.9°S; 14.3°W), São João do Cariri (7.4°S ; 36.5°O) and Costa Rica (9.7°N; 83°O). With this, the analysis of these datas in the mesospheric winds will be carried out through computational tools to obtain possible planetary waves for the zonal wind and meridional wind for the month of December of the year 2005. With the analysis performed, energy spectrum oscillations were detected only for the meridional wind in Ascension Island and São João do Cariri. The oscillations found are wave signatures with periods of 3-4 days for the meridional wind component. Through these observed oscillations their amplitudes and phases will be calculated for each altitude where they were identified, the vertical wavelength, the propagation speeds of the wave and the horizontal wavelength. Soon after, a study will be carried out on the behavior and characteristics of these waves with other works already carried out, in order to identify them to which category of waves they fit.